First record of the genus Eucremastus Szépligeti, 1905 (Hymenoptera: Ichneumonidae: Cremastinae) from the Arabian Peninsula, with the description of three new species - Gadallah, Neveen S.; Soliman, Ahmed M.; Dhafer, Hathal M. Al (Zootaxa, 2017)
The genus Eucremastus Szépligeti, 1905 (Hymenoptera: Ichneumonidae: Cremastinae) is recorded for the first time for the Arabian Peninsula from the Kingdom of Saudi Arabia. The present study is based on specimens collected from Al-Khararah, Rawdhat Al-Harmalyiah, Rawdhat Al-Sabalh, Rawdhat Farshet Sheaal and Wadi Ghaihab (Riyadh region, Central of Saudi Arabia). Three new species, E. arabicus Gadallah & Soliman, E. flavus Gadallah & Soliman and E. rufoantennalis Gadallah & Soliman are described and illustrated. An illustrated key to species is also provided.